PLGA-Based Nanoplatforms in Drug Delivery for Inhibition and Destruction of Microbial Biofilm - Shariati, Aref; Chegini, Zahra; Ghaznavi-Rad, Ehsanollah; Zare, Ehsan Nazarzadeh; Hosseini, Seyed Mostafa (Frontiers in Cellular and Infection Microbiology, 2022)
The biofilm community of microorganism have been identified as the dominant mode of microbial growth in nature and a common characteristic of different microorganism such as Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus epidermidis and Candida species. Biofilm structure lead to the protection from environmental threats including host immune system and antimicrobial agents. Therefore, biofilm community lead to the higher prevalence of multi-drug resistance strains in recent years. In this regard, the use of new class of antibiotics, natural compounds and anti-biofilm enzymes have been considered for destruction of microbial biofilm. However, different drawbacks such as low penetrations, high susceptibility to degradation, instability as well as poor solubility in aqueous solution, limit the use of anti-biofilm agents (ABG) in clinical setting. Therefore, scientists are interest in to use of PLGA (poly lactic-co-glycolic acid)-based drug systems for delivery of ABG and promising results also have been reported. PLGA-based platforms due to the proper drug loading and release kinetic, suppressed microbial attachment, colonization and biofilm formation for long time. Additionally, this platform because of the worthy size lead to the sufficient penetration of ABG to the deeper layer of the biofilm, consequently eliminated microbial biofilm. Therefore, PLGA-platforms could be considered as a potential candidate for coating catheter and other medical materials surface. However, the exact interaction of PLGA-platforms and microbial biofilm should be evaluated in the animal studies; additionally, a future goal will be to develop PLGA formulations as systems that can be used for the treatment of biofilm-associated infections such as cystic fibrosis, wound infection and oral disorders.